The Effectiveness Of Dry Needling Versus Muscle Energy Technique Combined With Ultrasound Therapy In Reducing Disability Due To Tennis Elbow - Putu Ayu Sita Saraswati; Sayu Aryantari Putri Thanaya; Made Hendra Satria Nugraha (Poltekkes Kemenkes Surakarta, 2022)
Background: The tennis elbow is the most frequently diagnosed condition in the elbow and the most common cause of musculoskeletal pain in the elbow. Pain, limitation of joint motion, decreased muscle strength, and activity limitations as well as obstacles in participating in life are caused by tennis elbow. The aim of this study was to compare the effectiveness of ultrasound therapy and dry needling versus ultrasound therapy and MET in reducing disability due to tennis elbow. Methods: This research was a randomized controlled trial using a pre and post-test control group design. The participants were 24 people who were divided into 2 groups. Group 1 (n = 12) was given the combined interventions of ultrasound therapy and dry needling, while group 2 (n = 12) was given the combined interventions of ultrasound therapy and MET. The interventions were given 12 times. Disability was measured using the Patient-Rated Tennis Elbow Evaluation Questionnaire (PRTEE). This study was conducted in the physiotherapy private practices in Denpasar and Badung Regency in Bali. Results: The result showed that the disability significantly decreased before and after the intervention in both groups (p<0.05). There was also a significant difference between the two groups. Conclusion: It can be concluded that ultrasound therapy and dry needling are more effective than ultrasound therapy and MET in reducing disability due to tennis elbow.